Обгрунтування рівня компенсації реактивної потужності для систем підземного електропостачання шахт - Півняк, Г.Г.; Заїка, В.Т.; Самойленко, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The energy-saving potential from the reduction of reactive energy flows in all electrical energy distribution steps in a mining underground power-supply system is estimated. A technical economic model is worked out, and the criterion of estimating the reactive power compensation efficiency and the compensation level under service conditions are grounded. The model stability to the variation of the objective compensative plant capacity is investigated. The sensitivity of the model to the basic data error is analyzed.